Foreign capital flows in Trinidad and Tobago : experience, macroeconomic impacts, and policy responses - Harripaul, Arjoon (Caribbean Centre for Monetary Studies [St. Augustine]TT, 1997)
focuses on the capital inflows and macro-economic developments in Trinidad and Tobago and discusses policy responses to capital inflows.